A comparison of the projected and the perceived image of Cyprus - Farmaki, Anna (My University, 2012)
The purpose of this research is to identify and compare the projected and perceived images of Cyprus following repositioning. Secondary sources such as brochures, advertising campaigns and tourism websites were used to identify the projected image and a survey was performed to measure the perceived image. Questionnaires including closed and open-ended questions evaluating destination attributes and perceived image were disseminated to 393 British tourists. The research identified the differences between the two concepts, revealing that the marketing strategy of Cyprus has not managed to enhance destination image. The paper concludes with recommendations on marketing Cyprus tourism
Keywords: Cyprus; Destination image; Tourism marketing